THE RELATIONSHIP OF THE WORK SAFETY PROGRAMS IMPLEMENTATION WITH THE PRODUCTIVITY OF EMPLOYEES IN PACKER PARTNERS PT. SEMEN BOSOWA MAROS - Ani Asriani Basri; Hasbi Ibrahim (Journal of Industrial Hygiene and Occupational Health, 2018)
The application of work safety programs is one form of the company's efforts to create safe and healthy workplace conditions for the workforce, so as to reduce absenteeism and increase employee productivity.This study aims to find out how the "Relationship between Work Safety Program Implementation and Employee Productivity in the Packer Section of PT. Semen Bosowa Maros”. This type of research is a type of quantitative research, namely an analytical survey. This study uses an analytic international design with a cross sectional study approach. With a sample of 48 respondents in the cement filling packer section with sampling, the total sampling method. Data obtained from the results of questionnaires, observations, and interviews. Then the data will be analyzed using chy-square analysis and fisher's excat to see the relationship between the dependent variable and the independent variable. Fisher's exact statistical test results obtained p value = 0.650> 0.05, this shows that there is no relationship between the knowledge of safety signs with the achievement of cement filling targets, obtained p value = 0.369> 0.05 which indicates that no there is a relationship between the frequency of health and safety training with the achievement of cement filling targets. With the chy-square statistical test, the value of p = 0.04 <0.05 indicates that there is a relationship between the use of personal protective equipment and the achievement of cement filling targets. It is necessary to install safety signs in the packer section to improve and foster awareness of the workforce in protecting themselves, improve K3 training and provide strict sanctions to workers who are not disciplined in using complete personal protective equipment.Keywords: Safety Program, Work Productivity, Packer Worker